Key access and utilization descriptors for wheat genetic resources - Bioversity International; International Center for Tropical Agriculture (2009)
This list consists of an initial set of characterization and evaluation descriptors for wheat utilization. This key set of strategic descriptors, together with passport data, will become the basis for the global accession-level information system being developed by the Bioversity-led project, Global Information on Germplasm Accessions (GIGA). It will facilitate access to and utilization of wheat accessions held in genebanks and does not preclude the addition of further descriptors, should data subsequently become available.